Mapping the helix model of innovation influence on education: A bibliometric review - Zakaria, Haziman; Kamarudin, Diyana; Fauzi, Muhammad Ashraf; Wider, Walton (Frontiers in Education, 2023)
As a direct result of the increased significance of knowledge in the various endeavours attempting to implement the triple helix model, higher education institutions have assumed a more prominent position in the processes involved in regional innovation and development. Expanding study on the helix model is currently examining the underlying causes and consequences of the evolution of the helix model in education. This research examines the relationship between the double helix model and the educational literature by using bibliometric analysis on 227 articles subjected to peer review between 1970 and 2022. This investigation concentrated on three aspects of analysis: (1) document citation via the use of co-citation analysis that produce 4 clusters; (2) document cited reference through the utilisation of bibliographic coupling that generates 5 clusters; and (3) document keyword through the utilisation of co-word analysis with 4 cluster. These results are important for academics, practitioners, and other interested parties who are working to improve the helix model for policymakers by putting it into an education strategy.